Implementation of Quadcopter for Capturing Panoramic Image at Sedayu Bantul - Anton Yudhana; Nuryono Satya Widodo; Sunardi Sunardi (ICON-CSE, 2014)
The aims of this study to deploy an aerial photography system has the ability to capture panoramic image of specific area. The planned research activities completed within 2 years, with the first year's target is Quadcopter design and manufacture that is equipped with a camera for image acquisition process. Target for the second year is shooting and processing panoramic images thus obtained are accurate. The steps to implement this study are divided into two parts: 1) the design and manufacture of quadcopter and 2) implementation of image capture and processing. The expected results of the study is the automated system  that have capability of imaging an area and perform image stitching on the imaging results so obtained image represents an area with a particular area with an adequate level of resolution. Thus this system can be referred for the next advance that is more complex for example: prediction system of agricultural crops with aerial photography, residential density estimation system with aerial photos, and hazard mitigation systems by using aerial photographs. The preliminary result of this research is panoramic images capturing with quadcopter. Quadcopter could flight as high as 6 meters for 3 minutes. Improvement is expected to reach flight  capability of quadcopter as high as 100 m within 10 minutes flight time minimum.